De Novo Versus Secondary Metastatic EGFR-Mutated Non-Small-Cell Lung Cancer - Bozorgmehr, Farastuk; Kazdal, Daniel; Chung, Inn; Kirchner, Martina; Magios, Nikolaus; Kriegsmann, Mark; Allgäuer, Michael; Klotz, Laura V.; Muley, Thomas; El Shafie, Rami A.; Fischer, Jürgen R.; Faehling, Martin; et al. (Frontiers in Oncology, 2021)
Background Metastatic epidermal growth factor receptor-mutated (EGFR+) non-small-cell lung cancer (NSCLC) can present de novo or following previous nonmetastatic disease (secondary). Potential differences between these two patient subsets are unclear at present. Methods We retrospectively analyzed characteristics of tyrosine kinase inhibitor (TKI)-treated patients with de novo vs. secondary metastatic EGFR+ NSCLC until December 2019 (n = 401). Results De novo metastatic disease was 4× more frequent than secondary (n = 83/401), but no significant differences were noted regarding age (median 66 vs. 70 years), sex (65% vs. 65% females), smoking history (67% vs. 62% never/light-smokers), and histology (both >95% adenocarcinoma). Patients with secondary metastatic disease showed a better ECOG performance status (PS 0–1 67%–32% vs. 46%–52%, p = 0.003), fewer metastatic sites (mean 1.3 vs. 2.0, p < 0.001), and less frequent brain involvement (16% vs. 28%, p = 0.022) at the time of stage IV diagnosis. Progression-free survival (PFS) under TKI (median 17 for secondary vs. 12 months for de novo, p = 0.26) and overall survival (OS, 29 vs. 25 months, respectively, p = 0.47) were comparable. EGFR alterations (55% vs. 60% exon 19 deletions), TP53 mutation rate at baseline (47% vs. 43%, n = 262), and T790M positivity at the time of TKI failure (51% vs. 56%, n = 193) were also similar. OS according to differing characteristics, e.g., presence or absence of brain metastases (19–20 or 30–31 months, respectively, p = 0.001), and ECOG PS 0 or 1 or 2 (32–34 or 20–23 or 5–7 months, respectively, p < 0.001), were almost identical for de novo and secondary metastatic disease. Conclusions Despite the survival advantage reported in the pre-TKI era for relapsed NSCLC, molecular features and outcome of TKI-treated metastatic EGFR+ tumors are currently independent of preceding nonmetastatic disease. This simplifies design of outcome studies and can assist prognostic considerations in everyday management of patients with secondary metastatic EGFR+ tumors.